Intravenous thrombolysis for large vessel or distal occlusions presenting with mild stroke severity. (23rd March 2020) - Tsivgoulis, G.; Goyal, N.; Katsanos, A. H.; Malhotra, K.; Ishfaq, M. F.; Pandhi, A.; Frohler, M. T.; Spiotta, A. M.; Anadani, M.; Psychogios, M.; Maus, V.; Siddiqui, A.; et al.
Abstract : Background and purpose: We investigated the effectiveness of intravenous thrombolysis (IVT) in acute ischaemic stroke (AIS) patients with large vessel or distal occlusions and mild neurological deficits, defined as National Institutes of Health Stroke Scale scores < 6 points. Methods: The primary efficacy outcome was 3‐month functional independence (FI) [modified Rankin Scale (mRS) scores 0–2] that was compared between patients with and without IVT treatment. Other efficacy outcomes of interest included 3‐month favorable functional outcome (mRS scores 0–1) and mRS score distribution at discharge and at 3 months. The safety outcomes comprised all‐cause 3‐month mortality, symptomatic intracranial hemorrhage (ICH), asymptomatic ICH and severe systemic bleeding. Results: We evaluated 336 AIS patients with large vessel or distal occlusions and mild stroke severity (mean age 63 ± 15 years, 45% women). Patients treated with IVT ( n  = 162) had higher FI (85.6% vs. 74.8%, P  = 0.027) with lower mRS scores at hospital discharge ( P  = 0.034) compared with the remaining patients. No differences were detected in any of the safety outcomes including symptomatic ICH, asymptomatic ICH, severe systemic bleeding and 3‐month mortality. IVT was associated with higher likelihood of 3‐month FI [odds ratio (OR), 2.19; 95% confidence intervals (CI), 1.09–4.42], 3‐month favorable functional outcome (OR, 1.99; 95% CI, 1.10–3.57), functional improvement at discharge [common OR (per 1‐point decrease in mRS score), 2.94; 95% CI, 1.67–5.26)] and at 3 months (common OR, 1.72; 95% CI, 1.06–2.86) on multivariable logistic regression models adjusting for potential confounders, including mechanical thrombectomy. Conclusions: Intravenous thrombolysis is independently associated with higher odds of improved discharge and 3‐month functional outcomes in AIS patients with large vessel or distal occlusions and mild stroke severity. IVT appears not to increase the risk of systemic or symptomatic intracranial bleeding.